Gambaran Status Gizi Pasien Tuberculosis Paru Dewasa Puskesmas Bayung Lencir Kabupaten Musi Banyuasin - Rinaldi, Riki; Indra, Silvia; Putri, Ega Irma (JURNAL KESEHATAN TERAPAN, 2024)
Tuberculosis is an infectious disease caused by the presence of Mycobacterium tuberculosis. One of the influencing factors is nutritional status. Poor nutritional status can exacerbate the risk of pulmonary tuberculosis. Likewise, Tuberculosis can affect food intake and then cause weight loss so that it affects nutritional status.The condition of Pulmonary Tuberculosis patients with poor nutritional status will inhibit healing and increase mortality compared to Pulmonary Tuberculosis patients with normal nutritional status. This study aims to describe the nutritional status of adult pulmonary tuberculosis patients at the Bayung Lencir Public Health Center, Musibanyuasin Regency. Analytical (qualitative) descriptive research using the simple random sampling method, in order to obtain 30 samples. The results showed that there were 20 male tuberculosis patients and 10 female patients. Tuberculosis patients of productive age from 26-45 years as many as 30 people. The nutritional status of Tuberculosis patients was measured using BMI (body mass index) with normal nutritional status as many as 12 people (40.0%), underweight nutritional status as many as 17 people (56.7%), and obesity nutritional status as many as 1 person (3.3 %). From this study, it was concluded that tuberculosis patients at the Bayung Lencir Public Health Center, Musibanyuasin Regency, on average had a nutritional status below normal (less).